Implementation of Appropriate Marketing and Sales Strategies in Improving Company Performance and Profits - Finny Redjeki; Haris Fauzi; Sidik Priadana (International Journal of Science and Society, 2021)
Every company has a goal of getting a specific profit or as much as possible and maintaining or even trying to increase it for the long term. This goal can be realized if the sale can be carried out as planned. Thus it does not mean that the goods or services sold will always generate profits, so the above factors must receive full attention for the company. Superior competence in understanding customers and, therefore, the opportunity to provide satisfaction to customers and the ability to recognize competitors' movements. Companies that manage to control the market and this arena are called market-driven firms that balance these two orientations well to produce better marketing performance than companies with other directions. Coordination between the company's functions as an effort, for example, to share information about customers and competitors with all tasks better to face the growing competition from time to time.